USED TIRE ECOSYSTEM FOR THE RECLAIMED RUBBER INDUSTRY DEVELOPMENT AT PT BRIDGESTONE TIRE INDONESIA - Suparno, Ono; Suprihatin; Indrasti, Nastiti Siswi; Hardjomidjojo, Hartrisari; Sunarti, Titi Candra; Utomo, Prasetyo Hadi; Yulistika, Efri; Triyonggo, Yunus; Matasik, Delfania (Department of Agroindustrial Technology, Bogor Agricultural University, 2025)
Managing end-of-life tyres (ELTs) has become an urgent global issue because tyres are difficult to decompose naturally and take more than 50 years to break down. In the Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) area, ELT generation is estimated at 2.5–3 million units annually, with the most significant contributions from Karawang (1,000 units per month) and Bogor (820 units per month). Bias-ply used tires, which contain up to 70% rubber, have significant potential for recycling into raw materials for new tires through reclaimed rubber technology, aligning with the principles of a circular economy. This study aims to map the supply chain ecosystem of ELTs, identify key stakeholders, and optimise material flow to support the development of the rubber industry from reclaimed materials. The study employs a qualitative descriptive method. The number of research locations was determined using the Solvin method with an error rate of 25%. Observations were performed at 15 specific tire shops, two truck tire shops, three fleets, and three used tire collectors in the Jabodetabek and West Java areas. The findings indicate that the total estimated number of ELTs collected in Jabodetabek from tire stores, truck tires, fleets, and collectors reaches 2,860 monthly units. The main challenges in ELT management include limited storage facilities, low awareness of the economic value of waste, and a predominantly conventional management system. The study also reveals that only 20% of ELTs are utilised optimally, highlighting a significant untapped potential. Keywords: used tires, reclaimed rubber, supply chain, circular economy